On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region - Calder, Dale R. (Zootaxa, 2012)
An account is given of 48 species identified in a small collection of hydroids from the west coast of Sweden. Assigned to39 genera and 18 families, most are well-known from boreal waters of the North Atlantic Ocean. Campanulina paniculaG.O. Sars, 1874 is referred to Racemoramus, a new genus of leptothecates distinguished in part by having monopodialgrowth, rigid and non-segmented hydrocauli, and grape-like clusters of hydrothecae that arise at irregular intervals fromthe stem. The name Sertularia dumosa (now Lafoea dumosa) is taken to have been made available by Fleming (1820), notFleming (1828). As such, it is not threatened by a virtually unused subjective synonym (Lafoea cornuta Lamouroux,1821). Aselomaris michaeli Berrill, 1948 and Rhizorhagium navis Millard, 1959 are regarded as synonyms and combinedunder the binomen Pachycordyle michaeli (Berrill, 1948). Confusion in the literature over the identity of Sertularia teneraG.O. Sars, 1874 is addressed, and distinctive characters of the species are discussed. A species often misidentified as S.tenera is assigned to Sertularia spitzbergensis (Jäderholm, 1909); the name spitzbergensis is elevated in rank from sub-specific to specific, and assigned priority over its simultaneous synonym siberica Jäderholm, 1909 under the First ReviserPrinciple. Gonothecae of Clytia gigantea (Hincks, 1866) (type locality: Lamlash Bay, UK) are reported for the first timein material from Europe. Although much like Clytia hemisphaerica, this species is retained as valid due to its remarkablyrobust colony form, elongate and gradually tapered hydrothecae, and linguiform rather than wavy or pointed marginalcusps. Eudendrium album Nutting, 1896, Pachycordyle michaeli (Berrill, 1948), and the hydroid stage of Halitholus cir-ratus Hartlaub, 1913 are reported for the first time from the study area. A checklist of hydroids from the study area is included.